Measuring Competition in Slovenian Industries Estimation of Mark-ups - Molnar, Margit (OECD Economics Department Working Papers, 2010)
Product market regulation on average is Slovenia does not appear particularly stringent, but heavy state involvement and high market concentration in several industries call for the gauging of competitive pressures in Slovenian industries. Owing to such characteristics, more sophisticated measures than the simple comparison of relative price levels is needed. Mark-ups can provide valuable information on competitive pressures in various sectors of the economy, reflecting pressures stemming from rules of conduct imposed by regulators as well as those arising from such factors as trade and FDI or increasing consumer demands in terms of price and quality. Conversely, the lack of competitive pressure may stem from heavy state involvement in the manufacturing and service sectors. This study is a first attempt to estimate mark-ups for manufacturing and service industries in Slovenia and in addition, its novelty is that it i) estimates mark-ups at a detailed level of sectoral disaggregation and ii) allows for non-constant returns to scale. The estimation is done for the period 1993-2006 and uses firm level data of the Amadeus database. In general, the estimated mark-ups are higher for services than manufacturing industries, but some manufacturing industries have high mark-ups in international comparison. This Working Paper relates to the 2009 OECD Economic Survey of Slovenia (www.oecd.org/eco/surveys/slovenia)